Muslim communities in England, 1962-92: multiculturalism and political identity - Fazakarley, J; Dr Jed Fazakarley (2014)
Since the conflicts in the Gulf and Bosnia in the 1990s, and the terrorist attacks of 9/11 and 7/7, a large sociological and political literature on British Muslims has appeared. It is often a contention of these works that Muslims in Britain did not identify, and were not seen in terms of, their religion prior to the time of the Rushdie affair. This thesis contends that, contrary to these arguments, religion has been a significant referent for the claims-making of Muslim communities in England since essentially the time that those communities settled (the early 1960s). This is demonstrated through the consideration of Muslim claims-making and elite practice and policy in a number of thematic areas, including education, employment, social services, and party politics. Building on these insights, it is suggested that such misconceptions about English Muslim social and political mobilisations are attributable to the absence of an historical perspective upon British multiculturalism. This thesis, particularly in two concluding chapters, attempts to correct this absence, offering a broader consideration of British multiculturalism in the studied period. It suggests that – rather than a relatively coherent ideology or policy approach – British multiculturalism has been an institution, produced in an ad hoc manner through the largely uncoordinated actions of a large number of actors, often lacking shared aims, at both local and national level. Although subject to changes over time, this institution has observed a number of consistent ‘rules’ in the form of concepts shared by actors involved in it (such as the ‘ethnic group, ‘community leadership’ and ‘special needs’). Finally, it is suggested that multiculturalism in Britain has endured primarily due to a process of ‘path dependence’ through which many actors have ‘learned’ how to operate within the rules of the institution, and may owe their existence of prestige to it.